The Effect Of Firm Size, Intellectual Capital, And Institutional Ownership On Company Value (Study On The Energy Sector Listed On The Indonesia Stock Exchange In 2018-2021) - Suzan, Leny; Kania, Triasafa (UNIVERSITAS PAKUAN, 2023)
Firm value is an important indicator for investors to consider whether to invest in a company or not. It is also a measure of how well the company is performing. The independent variables that I use are company size (UP), intellectual capital (IC), and institutional ownership (KI). The dependent variable is the company's value. The study was conducted on 13 energies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2021. The research data used a purposive sampling method to collect 52 observational data over 4 years. They used panel data regression analysis in Eviews 12 to analyze the data. The results of the study show that firm size, intellectual capital, and institutional ownership have a simultaneous effect on firm value. However, only firm size has a significant positive effect on firm value. Intellectual capital and institutional ownership have no partial effect on firm value. The researchers concluded that firm size is the most important factor influencing firm value. They also suggest that future studies should focus on the relationship between intellectual capital and institutional ownership and firm value.